2017
DOI: 10.7904/2068-4738-viii(16)-39
|View full text |Cite
|
Sign up to set email alerts
|

Content of Β–glucan in cereals grown by organic and conventional farming

Abstract: Abstract. In this paper, the results obtained from the investigations performed on determination of the content of soluble dietary fibre component β-glucan in different cereals grown by conventional and organic farming method are presented. Because dietary fibre and its components have great importance for human and animal nutrition as well as health benefits, it was a need to investigate the content of β-glucan from cereal domestic origin. Standardized enzymatic-gravimetric method-a mixed-linkage β-glucan ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…The highest amount of beta‐glucan was found in the Loot Hulless barley to be 3.5 ± 0.5% and 4.4 ± 0.4% with experiment and kit, respectively. This figures are in agreement with published papers which revealed that content of beta‐glucan in barley was 3.44% (Menkovska et al., 2017), 4.18% (Havrlentova & Kraic, 2006), and 4.6% (Demirbas, 2005). The content of beta‐glucan in wheat was 1.3 ± 0.1% with experiment and 1.5 ± 0.1% with kit.…”
Section: Resultssupporting
confidence: 92%
“…The highest amount of beta‐glucan was found in the Loot Hulless barley to be 3.5 ± 0.5% and 4.4 ± 0.4% with experiment and kit, respectively. This figures are in agreement with published papers which revealed that content of beta‐glucan in barley was 3.44% (Menkovska et al., 2017), 4.18% (Havrlentova & Kraic, 2006), and 4.6% (Demirbas, 2005). The content of beta‐glucan in wheat was 1.3 ± 0.1% with experiment and 1.5 ± 0.1% with kit.…”
Section: Resultssupporting
confidence: 92%
“…Significantly higher protein contents were reported for spelt than for common wheat, but there were no differences between conventional and organic farming systems [1]. Menkovska et al [29] reported a higher β-glucan content in conventionally grown barley (34.4 and 33.3 mg/g DM) and oat grains (23.5 and 21.3 mg/g DM) compared with those grown organically. However, the β-glucan contents were significantly higher in barley (42.6-58.4 mg/g DM) and oat grains and groats (34.5-68.4 mg/g DM) in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Some researchers found more soluble fiber in organically grown wheat [ 113 ], while some found such in conventionally grown wheat [ 105 ]. Slightly higher β-glucan content was found in organically than in conventionally grown wheat [ 114 ]. On the other hand, better antioxidant capacity and higher alkylresorcinol content [ 112 ] were found in organically grown durum wheat [ 115 ].…”
Section: Discussionmentioning
confidence: 99%